Consolidating Macroeconomic Adjustment in Brazil - de Mello, Luiz (OECD Publishing, 2006)
Brazil has made considerable progress in recent years towards consolidating macroeconomic stability, which is a key framework condition for sustained growth. Monetary policy continues to respond swiftly to changes in the inflation outlook, anchoring expectations. Fiscal policy has been guided by debt sustainability considerations, delivering primary budget surpluses that have often exceeded the end-year targets. Nevertheless, while the public debt-to-GDP has been reduced, it remains high, especially in comparison with other emerging-market economies. Brazil?s overarching macroeconomic challenge is therefore to continue to reduce the public debt overhang while improving the quality of fiscal adjustment, which has so far been underpinned by revenue hikes, rather than a retrenchment of expenditure commitments. To do so, measures will need to be taken to arrest the increase in current spending, especially on pensions, paving the way for subsequently removing distortions and reducing the tax burden over the medium to longer term, once the debt-to-GDP ratio has been reduced in a sustainable manner. The favourable domestic macroeconomic environment, with falling inflation and improving growth prospects, appears propitious for reform towards the gradual phasing-out of directed credit and a reduction in compulsory reserve requirements
Keywords: Economics; Brazil